Expression of CD34, DOG1, S100 in CD117-negative and CD117-positive gastrointestinal stromal tumors with different potential of malignancy and clinical, morphological features - V. R. Skorik (Patologìâ)
Diagnosis verification of gastrointestinal stromal tumor (GIST) requires thorough differential diagnosis and determination of malignancy potential.